2018
DOI: 10.1039/c7sc05227h
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected solvation-stabilisation of ions in a protic ionic liquid: insights disclosed by a bond energetic study

Abstract: Accurate acidity studies of different families of substrates in a pure protic ionic liquid (PIL) show that solute ions in the PIL are free from specific ion associations and the solvation behaviour of PILs is closely related to the number of dissociable protons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The experiments and spectrum results indicated that the DBPILs 1f could addition to 2f and further generate 1h with a hydroxyl group, because of the "super-dissociating" feature of the protic ionic liquids. 72 Furthermore, 1h could not activate CO2 and had a relatively weak H-bond interaction with epoxide compare to the powerful H-bonding of 1f, which led to the reduction of the yields in the recycle experiments. energy of ring-opening step.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments and spectrum results indicated that the DBPILs 1f could addition to 2f and further generate 1h with a hydroxyl group, because of the "super-dissociating" feature of the protic ionic liquids. 72 Furthermore, 1h could not activate CO2 and had a relatively weak H-bond interaction with epoxide compare to the powerful H-bonding of 1f, which led to the reduction of the yields in the recycle experiments. energy of ring-opening step.…”
Section: Resultsmentioning
confidence: 99%
“…The regression analyses show that the acidities of structural and electronic different organic substrates, i.e., RO-H, N-H, N + -H, and RCOO-H, linearly correlate with those in water. However, instead of forming a unified straight line, which is the case found for the analogous acidity correlation between a PIL EAN (ethylammonium nitrate) and water (Kanzaki et al, 2016), each individual series exhibits different slope and intercept (Figure 2) (Wang et al, 2018a). These linear acidity correlations between PILs and molecular solvent water are highly useful for accessing p K a values of compounds in neat PILs that are difficult to determine due to the solvent leveling effect.…”
Section: Resultsmentioning
confidence: 94%
“…In our previous work, we have successfully measured the acidities for several series of commonly seen organic acids in a DBU-based PIL, i.e., [DBUH][OTf] (OTf − = triflate) (Wang et al, 2018a). The regression analyses show that the acidities of structural and electronic different organic substrates, i.e., RO-H, N-H, N + -H, and RCOO-H, linearly correlate with those in water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and [DBUH][TfO] have been studied in the past by different groups 2,5,6,16,40. [DBUH][IM14] has been prepared for the first time in this report and no previous information exists on this PIL.…”
mentioning
confidence: 99%